2021
DOI: 10.33448/rsd-v10i5.14493
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic content and antioxidant and anticholinesterase activities of medicinal plants from the State’s Cocó Park (Fortaleza-CE, Brazil)

Abstract: The State’s Cocó Park in the city of Fortaleza-CE present mainly a mangrove flora and include landscape and medicinal plants. The aim of this study is determining the total phenol content, antioxidant activity against the free radical DPPH and the inhibition of the enzyme acetylcholinesterase (AChE) in ethanolic extracts of 30 medicinal plants and thus assess which plants have potential against Alzheimer's Disease.  The plants rich in phenolic compounds with amounts ranging from 297.46 ± 26.94 to 599.30 ± 17.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
1
5
0
1
Order By: Relevance
“…The authors found that extracts with the high content of total phenols had the highest antioxidant activity. [27] The antioxidant capacity of the extracts was quantified in terms of the median inhibitory concentration of the free radicals DPPH * and ABTS + * (IC 50 ). These methods have been widely used to determine the antioxidant action of plant products due to their easy execution, low cost, high sensitivity and speed.…”
Section: Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that extracts with the high content of total phenols had the highest antioxidant activity. [27] The antioxidant capacity of the extracts was quantified in terms of the median inhibitory concentration of the free radicals DPPH * and ABTS + * (IC 50 ). These methods have been widely used to determine the antioxidant action of plant products due to their easy execution, low cost, high sensitivity and speed.…”
Section: Compoundsmentioning
confidence: 99%
“…The most common compounds are phenolic acids, flavonoids, carotenoids, and vitamins C and E. A study carried out with medicinal plants from Cocó State Park in the city of Fortaleza, Ceará, Brazil, indicated that species with high antioxidant capacity also had in vitro anticholinesterase activity. [27] The anticholinesterase capacity of the extracts was quantified as the median inhibitory concentration of the AChE enzyme and the results obtained were compared to those of the alkaloids physostigmine (the first natural inhibitor discovered) and galantamine (among the natural alkaloids most used as a standard drug against AD). [30] In the anti-AChE test, the samples had IC 50 values ranging from 6.02 to 10.92 μg mL À 1 , and PEE presented the best result.…”
Section: Compoundsmentioning
confidence: 99%
“…Plants with high levels of phenolic compounds such as Anacardium occidentale, Ceiba pentandra, Laguncularia racemosa, Mangifera indica, Myracrodrum urundeuva and Terminalia catappa showed excellent antioxidant activity against the DPPH radical (with IC50 ranging from 3.44 ± 0.16 to 3.73 ± 0.12 µg mL -1 ) and high power of inhibition of the AChE enzyme (IC50< 20 μg mL -1 ) were recommended for more specific studies related to Alzheimer's disease [8].…”
Section: Original Research Articlementioning
confidence: 99%
“…Uma abordagem promissora no tratamento da doença de Alzheimer (DA) é o uso de produtos naturais que, ao inibir a enzima aceticolinesterase, aumentam níveis de acetilcolina e, consequentemente, revertem o déficit de memória, por tanto, medicamentos que têm a inibição da AChE como mecanismo de ação são chamados de anticolinesterase ou indiretamente colinérgicos (Morais de et al, 2021;Barbosa et al, 2006). Portanto, plantas que tenham de atividades acetilcolinesterásica, anti-inflamatória e antioxidante são potenciais fontes de tratamento para DA.…”
Section: Introductionunclassified